Intraductal Papilloma With Carcinoma of the Breast Described by Dedicated Breast 18F-FDG PET. (8th February 2022) - Noritake, Mutsumi; Yamada, Akimitsu; Yamanaka, Shoji; Utsunomiya, Daisuke; Inoue, Tomio
Abstract: Intraductal papilloma (IDP) is a benign tumor of the breast. However, IDP has been reported to show high uptake of 18 F-FDG using whole-body PET. We experienced IDP with low-grade ductal carcinoma in situ using dedicated breast PET, which is more sensitive than whole-body PET. The 18 F-FDG uptake of the whole tumor was high, and differentiation between the carcinoma and the residual benign lesion was difficult. This is the first report of IDP detected with dedicated breast PET. Diagnosis of IDP is sometimes controversial; papilloma may show glucose uptake similar to that of low-grade carcinoma.